2014
DOI: 10.1590/1678-4499.0127
|View full text |Cite
|
Sign up to set email alerts
|

Climate trends in a non-traditional high quality wine producing region

Abstract: The global warming may put pressure over some world's highest quality wine producing regions. This fact indicates the need to evaluate the presence of climate change in non-traditional wine producing regions of the Globe. Therefore, the goals of this study were to detect trends in rainfall and air temperature series obtained from three locations of the eastern part of the State of São Paulo, Brazil (a non-traditional high quality wine producing region) and to evaluate the effect of the detected climate trends … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
1
5
0
1
Order By: Relevance
“…In addition, the advance of the phenophases also resulted in a shortening of the growing cycle (up to 21 days between the present and the scenario corresponding to the year 2070 under the warmer conditions) and warmer conditions during ripening. The same effects were also confirmed in other areas for Tempranillo and other varieties (Bardin-Camparotto et al, 2014;Fraga et al, 2016;Pieri et al, 2012;Salazar Parra et al, 2010).…”
Section: Discussionsupporting
confidence: 80%
“…In addition, the advance of the phenophases also resulted in a shortening of the growing cycle (up to 21 days between the present and the scenario corresponding to the year 2070 under the warmer conditions) and warmer conditions during ripening. The same effects were also confirmed in other areas for Tempranillo and other varieties (Bardin-Camparotto et al, 2014;Fraga et al, 2016;Pieri et al, 2012;Salazar Parra et al, 2010).…”
Section: Discussionsupporting
confidence: 80%
“…The meteorological data (daily precipitation and air temperature) were obtained from the Agronomic Institute of Campinas (IAC/APTA/SAA). The weather stations (Figure ; 1960–2016) have been selected because they present virtually no missing data, and their consistencies were evaluated in previous studies (Blain et al ., ; Bardin‐Camparotto et al ., ). These eight weather stations are situated at experimental farms of the Department of Agriculture of the State of São Paulo (APTA/SAA) and have been routinely used in both academic and operational mode.…”
Section: Study Area Data and Methodsmentioning
confidence: 99%
“…As a result, the best wines of the world come from regions with a certain balance among the three climate attributes ( Schultz and Jones, 2010 ), traditionally found within 30–50°N and 30–40°S latitudes ( Jones, 2003 ; Nesbitt et al, 2018 ). However, many recent studies have reported an observed warming trend in most viticultural regions ( Jones, 2005 ; Neethling et al, 2012 ; Santos et al, 2012 ; Bardin-Camparotto et al, 2014 ; Kryza et al, 2015 ). A similar warming trend has been reported in MI ( Schultze et al, 2014 , 2016b ; Schultze and Sabbatini, 2019 ) and has been linked with the observed expansion in land suitability for both wine and table grapes ( Schultze et al, 2016b ; Wanyama et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…This part of the study borrowed from methodologies from Jones (2012) , Bardin-Camparotto et al (2014) , and Deitch et al (2017) . The Mann–Kendall test was performed to assess the presence, or lack thereof, of persistent monotonic trends in each variable TS.…”
Section: Study Area Data and Methodsmentioning
confidence: 99%
See 1 more Smart Citation